(untitled) (Revista Cientifica Ingenio Magno, 2021)
This article addresses the present need during the production of an axial fan in the testing stage, where, through a test bench, the performance of the fan is obtained to know its operating capacity and provide a reference for its selection in the required applications. Therefore, the present research aimed to design and build an axial fan test bench that allows obtaining the characteristic curve of the fan under test. To achieve this, it was designed under the AMCA 210 standard “Laboratory Methods of Testing Fans for Certified Aerodynamic Performance Rating” of the Air Movement and Control Association International, it was modeled using Autodesk Inventor to obtain the drawings that guided the construction, together with the corresponding selection of instrumentation according to the specifications of the standard and low cost materials available in the local industry. Finally, the standardized low-cost axial fan test bench was obtained, the first in the region, at the service of students and professors of the Faculty of Mechanical Engineering of the Santo Tomás University Tunja sectional.